Dame met het witte hoedje . The Lady with the White Hat - Horst, Aliona van der (NFTVA, 1997)
Verzio FF Submission Portrait of a Ukrainian woman in Odessa whose political convictions confined her to a psychiatric ward for seven years under Brezhnev and Andropov regimes. Hana is now a symbol for the victims of Soviet psychiatry for whom re-entry into society has been more than difficult.